Debt sustainability in Guatemala: Institutional arrangement and quantitative analysis - Juan Carlos Catalán-Herrera (Inter-American Development Bank (IDB), 2020)
This paper assesses debt sustainability in Guatemala. Debt stability has been achieved at very low expenditure levels, at the expense of adequate provisioning of public goods and services and a widening gap in social development and infrastructure. Since fiscal outcomes are not independent from fiscal policy arrangements and procedures, the paper also sets forth a hypothesis of possible institutional arrangements that have allowed for the containment of fiscal deficits for over 20 years. The paper argues that embedded in the legal framework and institutional arrangement, there is an 'implicit' fiscal rule that favors stability. The paper explores characteristics of how fiscal policy is conducted, showing that government expenditures are pro-cyclical, providing room for improvement in cycle management. Fiscal policy has been mainly concerned with stability rather than other possible goals like boosting long-run growth, attenuating business cycles, improving human development indicators, dealing with redistribution issues and other goals that fiscal policy could pursue.
Keywords: H62; H63; E62; E02; 330; Fiscal sustainability; Guatemala; Debt; Fiscal policy